2014
DOI: 10.1017/jfm.2014.324
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Taylor–Aris dispersion of an initial point concentration

Abstract: Based on the method of moments, we derive a general theoretical expression for the time-dependent dispersion of an initial point concentration in steady and unsteady laminar flows through long straight channels of any constant cross-section. We retrieve and generalize previous case-specific theoretical results, and furthermore predict new phenomena. In particular, for the transient phase before the well-described steady Taylor-Aris limit is reached, we find anomalous diffusion with a dependence of the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…There seems to be conflicting explanations about the role of CPS, which would have enough mixing effect in large plant cells; however, such a Péclet number scale possesses fully developed diffusion to the whole length of the Nitella internodal cell, ~1 cm, of approximately 44 days! On the other hand, dispersion in a pipe flow with a radial shear gradient, which is well known as the Taylor–Aris dispersion [ 31 ], works as a radial dispersion, and consequently it effectively provides a longitudinal diffusion as the effective dispersion coefficient [ 32 ], . Here, γ is the geometric factor that depends on the flow distribution and the boundary condition in the flow field, discussed in detail in S1 Text , as being , because D eff = 1.57 × 10 −9 m 2 s −1 and s. This means that dispersion with a velocity gradient in the cytosol is 356 times faster than molecule dispersion with a flattened velocity field because of the dispersion ratio D eff / D Brown = 356.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be conflicting explanations about the role of CPS, which would have enough mixing effect in large plant cells; however, such a Péclet number scale possesses fully developed diffusion to the whole length of the Nitella internodal cell, ~1 cm, of approximately 44 days! On the other hand, dispersion in a pipe flow with a radial shear gradient, which is well known as the Taylor–Aris dispersion [ 31 ], works as a radial dispersion, and consequently it effectively provides a longitudinal diffusion as the effective dispersion coefficient [ 32 ], . Here, γ is the geometric factor that depends on the flow distribution and the boundary condition in the flow field, discussed in detail in S1 Text , as being , because D eff = 1.57 × 10 −9 m 2 s −1 and s. This means that dispersion with a velocity gradient in the cytosol is 356 times faster than molecule dispersion with a flattened velocity field because of the dispersion ratio D eff / D Brown = 356.…”
Section: Discussionmentioning
confidence: 99%
“…2014; Yariv & Schnitzer 2014; Sandoval & Dagdug 2014; Makhnovskii 2019) have experimentally and numerically investigated the transient active dispersion process in a corrugated channel without background flow, considering the application of sorting particles by their self-propelled speeds. Additionally, it is of considerable interest to systematically compare the transient active dispersion process with the classic dispersion of passive particles (Lighthill 1966; Foister & van de Ven 1980; Latini & Bernoff 2001; Camassa, Lin & McLaughlin 2010; Vedel, Hovad & Bruus 2014; Taghizadeh, Valdés-Parada & Wood 2020), to capture the difference in approaching the Taylor dispersion regime (Chatwin 1970; Wu & Chen 2014; Li et al. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(2004), Zhao & Bau (2007) and Adrover (2013). While the aforementioned works were concerned with spatial inhomogeneities, the role of time-dependent flow profiles was discussed by Vedel & Bruus (2012) and Vedel, Hovad & Bruus (2014). Here, the authors showed that oscillations can enhance dispersion, given that the oscillation frequency is lower than the momentum and solute diffusion time scale over the channel cross-section.…”
Section: Introductionmentioning
confidence: 99%